PERKEMBANGAN TARI ILAU KREASI DI KENAGARIAN SALAYO KECAMATAN KUBUNG KABUPATEN SOLOK - Endang Nuryani; Indrayuda Indrayuda; Herlinda Mansyur (SENDRATASIK UNP, 2015)
Abstract This article aims to reveal and explain the impact of exploration methods for learning local dance elapsed areas. This research is a qualitative descriptive method. Data obtained by direct observation and interviews. Data were analyzed based on the phenomena that occur in learning, to interpret the relationship between the phenomena occurring in the learning. The results showed, exploratory methods in teaching dance at resulted in increased imagination and creative power and ability of the students in the birth of new motifs from local dance movement. Another impact is that students feel they have freedom of expression, and is able to explore the body with improvisation, so that ideas can create new movement patterns are used for local dance lessons.   Keywords: Ilau Dance Creation and development.